Book review: Residential child care: prospects and challenges Andrew Kendrick, Editor - Irene Stevens (Scottish Journal of Residential Child Care)
This book forms part of the useful Research Highlights series and addresses residential child care. The book is divided into four helpful sections that cover: wellbeing and development; discrimination; conflict and response; and context and culture. The first section devotes itself to health and education, transitions from care and working within a resilience framework. The second section deals with issues around gender, race, ethnicity and disability. The third section looks at conflict within residential care and is perhaps the most innovative section in the book. Excellent evidence-based discussions on restraint, peer violence and the use of secure accommodation are generally lacking in this area which is often, ironically, one where practitioners and policy makers seek most guidance. This area of the work can be very stressful for staff and young people alike and it is refreshing to see it discussed in such an objective way. The fourth section deals with children's rights, training and recruitment of staff, leadership and therapeutic approaches.